Functionalizing the γ-position of α-diazo-β-ketoesters. Issue 30 (27th July 2016) - Nguyen, Thu Q.; Alqurafi, Maha; Edwards, Cash; Nguyen, Pauline; Kim, Jean; Casco, Samuel; Bennet, Maricka; Chiang, Christopher; Lohry, Maureen; Cox, Melina; Meshram, Byron; Le, Duyen; et al.
Graphical abstract: Highlights: New and established methods for functionalizing α-diazo-β-ketoesters are evaluated. A new protocol for appending an allyl group to these compounds is developed. A new preparation of γ-heteroatom-substituted diazoketoesters is presented. The first δ-aldehydo-α-diazo-β-ketoesters are prepared. These new aldehydes undergo base-promoted rearrangement to pyrazoles. Abstract: Although α-diazo-β-ketoesters are synthetically versatile intermediates, methodology for introducing this functionality into complex molecules is still limited, most frequently involving a carboxylic acid precursor, which is then activated and transformed into a β-ketoester, with the diazo group being subsequently added with a diazo transfer reagent. While introducing this highly functional moiety in a convergent one step process would be ideal, such an objective is limited by the relatively few studies which address functionalization of the α-diazo-β-ketoester at the γ-position. In the present investigation, we evaluate strategies, both new and established, for functionalizing α-diazo-β-ketoesters, particularly with regard to generating compounds prospectively useful in the synthesis of C1-substituted carbapenems. We report the first δ-aldehydo-α-diazo-β-ketoester as well as a method for its oxidation to the corresponding methyl ester, and the formation of a new substituted pyrazole under basic conditions.